TRABALHO E PRECARIZAÇÃO SOCIAL NO CAPITALISMO CONTEMPORÂNEO: dilemas e resistência do movimento organizado de trabalhadores - Inez Stampa (Universidade Federal do Maranhão, 2018)
This reflection is based on a bibliographical review and in documentary sources. It takes work as a key category of historical understanding, indicating some dilemmas about union action in a context of restriction of rights and collective actions. Considering the importance to expand spaces for collective struggle in the dynamics of the organized workers movement in Brazil, it seeks to emphasize that such a movement can’t be thought only in the space of the world of work or even in the institutional space of professional relations. The extension of the field of action imposes itself, since the traditional action of trade unionism is insufficient to face the multiplicity of grounds, disputes and struggles that must be conducted outside of work, which are so numerous and complex that no organization can claim to assume them alone in times of intensification of neoliberalism.